2013
DOI: 10.1182/blood-2012-07-441857
|View full text |Cite
|
Sign up to set email alerts
|

CD59 deficiency is associated with chronic hemolysis and childhood relapsing immune-mediated polyneuropathy

Abstract: Key Points• A novel clinical syndrome is reported which is triggered by common febrile episodes in infancy and presents with Coombs' neg hemolysis and demyelineating polyneuropathy.• A gene mutation in CD59 leading to loss of expression of CD59 on the cell surface is presented as the genetic basis for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 24 publications
2
109
1
Order By: Relevance
“…Recently, it was reported that the deficiency of CD59 in the cell membrane due to the C89Y mutation in CD59 is associated with childhood familial chronic Coombs-negative hemolysis and relapsing immune-mediated polyneuropathy (23). However, the downregulation of CD59 is also involved in the pathogenesis of many human diseases to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the deficiency of CD59 in the cell membrane due to the C89Y mutation in CD59 is associated with childhood familial chronic Coombs-negative hemolysis and relapsing immune-mediated polyneuropathy (23). However, the downregulation of CD59 is also involved in the pathogenesis of many human diseases to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…From a functional point of view, this protein fold has proven highly versatile, as evolution has created single domain paralogs with such diverse functions as bona fide cytotoxins that inhibit acetylcholine esterases (fasciculins), ion channels (calciseptine) or nicotinic acetylcholine receptors (e.g., α-neurotoxins), inhibitors of autologous complement activation (CD59), cofactors of lipolysis enabling trans-capillary trafficking of lipoprotein lipase (GPIHBP-1), and maintenance of paracellular diffusion barriers in Drosophila by trafficking and assembly of septate junction components (crooked, crimpled, coiled, and boudin) (Kini and Doley 2010;Nilton et al 2010;Nevo et al 2013;Young and Zechner 2013). Nevertheless, the biochemical function of a large proportion of these single domain LU-proteins still remains enigmatic, as illustrated by the >20 murine Ly-6 antigens encoded on chromosome 15 and predominantly expressed by neutrophils (Lee et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Ly-6/uPAR (LU) protein domain superfamily is a welldefined group of functionally diverse proteins involved in a multitude of biological processes, as exemplified by their role in the toxic insult by snake venom α-neurotoxins (Kini and Doley 2010), maintenance of squamous epithelial integrity by SLURP-1 (Favre et al 2007), regulation of complement activation by CD59 (Nevo et al 2013), translocation of lipoprotein lipase across capillaries by GPIHBP-1 (Davies et al 2010;Young and Zechner 2013), cytokine signaling by TGF-β receptors (Hinck 2012), and focalizing cell-surface associated proteolysis by urokinasetype plasminogen receptor (uPAR) (Kriegbaum, Persson, et al 2011). The individual members of the LU-protein domain family share a relatively low overall sequence similarity as they are primarily defined by a consensus sequence motif encompassing eight cysteines arranged in a characteristic disulfide-bonding pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, rare cases of inherited mutations in CD59 leading to loss of CD59 on the cell surface have been well documented. 8,9 The phenotype of these patients mimics PNH in that they manifest chronic intravascular hemolysis with paroxysmal flares of hemolysis and a propensity for thrombosis. Unlike PNH, pedigrees with inherited CD59 deficiency also present with relapsing immunemediated peripheral neuropathy.…”
Section: Paroxysmal Nocturnal Hemoglobinuriamentioning
confidence: 99%